The Effectiveness of Arabic Learning Materials to Improve Students’ Listening Skills at Darussalam Islamic Boarding School - Subakir, Fairuz; Muflihah, Luthfiah; Halim, Fauzul; Nur Fauziah, Siti Anne Barkah; Adam, Shomuddin Birrir (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
Listening skill is one of the essential aspects of Arabic learning. There was no teaching material for Arabic listening skills in the form of books at Kulliyyatul Muallimin al-Islamiyyah (KMI) Gontor which lead to an imbalance of harmonies among four Arabic language skills. This article aimed to develop the teaching materials for listening skills after being tested based on the problem formulation. Using the ten-stage Borg and Gall development model, this article was a form of research and development (R&D). Data for the Wilcoxon formula analysis was acquired from Gontor Islamic Boarding School in Ponorogo, Indonesia, through observation, interviews, questionnaires, achievement tests, and documents. This article focused on 5th grade with a sample of 33 students for the first experiment and 60 students for the second experiment implementing stratified random sampling. The result showed that textbook form for Kulliyyatul Muallimin al-Islamiyyah (KMI) Gontor at the 5th grade for listening teaching materials was effective in developing Arabic skills ability. According to the data, student listening skills have improved by 60.12%. Due to this learning material effectiveness, it is essential for educators, institutions, and students to maximize the use of this material in order to collaborate on enhancing Arabic language proficiency.